Relationship Between CRB-65 Score and Mortality in Pneumonia Patient at RSUD Dr. H. Chasan Boesorie Ternate - S Arahman, Rohid; Handoko, Dwi; Nur Upik En Masrika (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Pneumonia is a serious form of acute lower airway infection in the lung parenchyma that has the potential to cause high morbidity and mortality. The substantial number of cases and visits emergency units and hospital admissions due to pneumonia makes the CRB-65 Score important in assessing the severity of pneumonia to reduce the risk of mortality. The purpose of this research is to find out knowing the relationship between CRB-65 score and mortality in pneumonia patients at RSUD Dr. Chasan Boesorie Ternate. This type of research is was a quantitative study using an analytical observational research with a cross sectional approach using fisher's exact test. The sample amounted to 70 samples taken using medical record data with total sampling technique. The characteristics of pneumonia patients out of 70 samples, 72.9% were <65 years old, 52.9% were male, 57.1% with mild score (score 0) as many as 40 patients, 62% of patients' mortality was alive. Based on bivariate analysis, the p-value = 0.001 (p<0.05). There is an association between CRB-65 score and mortality in pneumonia patients at RSUD Dr. H. Chasan Boesoirie Ternate.